South East Asia: Strengthening Farm - Agribusiness Linkages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Strengthening Farm-Agribusiness Linkages helps famers to build successful farm-agribusiness linkages, vital for agribusiness development. Small farmers have to be entrepreneurs in order to move beyond subsistence farming, and agribusiness companies need r